1997
DOI: 10.1007/s004390050413
|View full text |Cite
|
Sign up to set email alerts
|

Trp290Cys mutation in exon IIIa of the fibroblast growth factor receptor 2 (FGFR2) gene is associated with Pfeiffer syndrome

Abstract: Pfeiffer syndrome is a skeletal disorder characterized by craniosynostosis associated with foot and hand anomalies. Mutations in the genes encoding fibroblast growth factor receptors 1 and 2 (FGFR1 and FGFR2) have recently been implicated in the aetiology of such a syndrome, as well as of other craniosynostotic conditions. We now report a novel missense mutation, a G to C transversion at position 1049 (exon IIIa) of FGFR2, detected in a patient with severe Pfeiffer clinical features. The mutation results in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
1
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 36 publications
3
26
1
1
Order By: Relevance
“…[Robin et al, 2011]. Four types of FGFR2 mutations were detected in our study, all of which were identified previously [Rutland et al, 1995;Tartaglia et al, 1997;Gripp et al, 1998;Itoh et al, 2006]. In our series, FGFR2 mutations showed the same subtypes as reported by Cohen and the same phenotypic severity as reported previously for patients with identical mutations [Rutland et al, 1995;Tartaglia et al, 1997;Gripp et al, 1998;Itoh et al, 2006].…”
Section: Resultssupporting
confidence: 85%
“…[Robin et al, 2011]. Four types of FGFR2 mutations were detected in our study, all of which were identified previously [Rutland et al, 1995;Tartaglia et al, 1997;Gripp et al, 1998;Itoh et al, 2006]. In our series, FGFR2 mutations showed the same subtypes as reported by Cohen and the same phenotypic severity as reported previously for patients with identical mutations [Rutland et al, 1995;Tartaglia et al, 1997;Gripp et al, 1998;Itoh et al, 2006].…”
Section: Resultssupporting
confidence: 85%
“…Pfeiffer syndrome (PS; OMIM #101600) is an autosomal dominant disorder characterized by craniosynostosis, midface hypoplasia, broad thumbs, brachydactyly, broad great toes, and variable cutaneous syndactyly (Tartaglia et al, 1997;Kress et al, 2000;Teebi et al, 2002;Cohen, 2004). The premature fusion of one or more cranial sutures leads to an abnormal skull shape (Tartaglia et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The premature fusion of one or more cranial sutures leads to an abnormal skull shape (Tartaglia et al, 1997). There is considerable clinical heterogeneity and 3 subtypes of PS, with clinical overlap and with different prognostic trends (Cohen, 1993(Cohen, , 2004.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 Surprisingly, the same FGFR2 mutation can give rise to CS, PS or JW phenotype. 6,13 Until 2002, FGFR2 mutations had been identified almost exclusively in the extracellular domain of the receptor mainly in exons 8 (IIIa) and 10 (IIIc) encoding the third immunoglobulin-like (Ig III) loop and appeared to account for only 50% of CS and PS cases. 14 In 2002, novel mutations in other regions of the receptor including the IgII loop and the tyrosine kinase subdomains TK1 and TK2 have been reported.…”
Section: Introductionmentioning
confidence: 99%